2009
DOI: 10.1111/j.1365-2354.2008.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Art therapy improves experienced quality of life among women undergoing treatment for breast cancer: a randomized controlled study

Abstract: Women with breast cancer are naturally exposed to strain related to diagnosis and treatment, and this influences their experienced quality of life (QoL). The present paper reports the effect, with regard to QoL aspects, of an art therapy intervention among 41 women undergoing radiotherapy treatment for breast cancer. The women were randomized to an intervention group with individual art therapy sessions for 1 h/week (n = 20), or to a control group (n = 21). The WHOQOL-BREF and EORTC Quality of Life Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(141 citation statements)
references
References 32 publications
1
132
0
8
Order By: Relevance
“…One study was reported in three sources to use a 'trained' art therapist. [62][63][64] One study reported the art therapist as 'licensed'. 56 Two studies reported using a 'qualified' art therapist.…”
Section: Data Synthesismentioning
confidence: 99%
“…One study was reported in three sources to use a 'trained' art therapist. [62][63][64] One study reported the art therapist as 'licensed'. 56 Two studies reported using a 'qualified' art therapist.…”
Section: Data Synthesismentioning
confidence: 99%
“…Las aplicaciones en población clínica adulta ponen de manifiesto la utilidad de estas técnicas, por ejemplo, en pacientes diagnosticados de esquizofrenia (Patterson, Debate, Anju, Waller y Crawford, 2011), en madres con depresión leve y moderada postnatal (Perry, Thurston y Osborn, 2008), en pacientes con enfermedad de Alzheimer (Guetin et al, 2009), y en los efectos de los tratamientos y manejo de síntomas oncológicos (Monti et al, 2006;Öster et al, 2006;Svensk et al, 2009;Wood, Molassiotis y Payne, 2011), entre otros.…”
Section: Introductionunclassified
“…This kind of initiatives do not include people into culture producing process, rather it invites participants to revel cultural events together with other people despite they are participants of initiative or not, in other words -be part of natural audience. Despite active or passive participation in culture strengthens feeling of belonging to community, stimulates positive experience and feelings [24], any kind of relation between person and culture has a health benefits, despite of participating or attending culture. Cultural engaged social initiatives addressing health and QoL are found throughout the world: in Great Britain prescription of culture (2004) later (2010) recalled "Social Prescription" linked patients to participate in particular social actions (membership in social networks, volunteering clubs, etc.)…”
Section: Employment Of Culture For Social Involvement Of Patientsmentioning
confidence: 99%